Reimagining the New World Order Post-Covid-19 - Maqsood Hussain (Qubahan Academic Journal)
The Novel Corona Virus, 2019 (Covid-19) may prove a watershed moment in the history of international relations. As the Covid-19 rages, the USA and China are embroiled in deep political and strategic conflict. The paper argues that the long-standing tussle over control of global order will intensify and result in its major metamorphosis. It is further argued that changed geopolitical order will see a significant rise of China and the relative decline of the USA which will have far-reaching implications for the multilateral institutions and regimes, one of the special areas of focus of this paper. Though the relative balance of power will potentially shift in favor of China feeding the narrative of counter-hegemonic balancing, yet it would be misleading to conclude the demise of the US-led global order in the foreseeable future. I further argue that the potential and capability of China to dislodge the US from the superpower status and assume the leadership of global order is beset with tremendous roadblocks. The paper concludes with some policy insights for the US foreign policy as to how the rise of China can be tamed and accommodated in the existing order without involving the use of coercion or risking a great-power war.